INOVASI PIPER CLEAN SEBAGAI PEMBERSIH LANTAI - Sutanti; Salsabila, Nadia; C.B., Selva Ayu; A., Seroja Keyndi; B.B., Shella Amanda (Badan Perencanaan Pembangunan Daerah dan Penelitian dan Pengembangan Kabupaten Wonogiri, 2025)
The Piper Betle Linn, is a plant that originates from the tropical regions of Central and South America. Betel plants are known for their anti-inflammatory, antioxidant, and antibacterial properties, as well as their potential to treat a variety of health conditions, including stomach aches, digestive disorders, and respiratory infections. From the content contained in betel leaves that can be used as a bathroom cleaner is phenol. Phenols in betel leaves are kavikol and kavibetol, which have antiseptic, antioxidant, and fungicidal power with antibacterial activity six times more effective than ordinary fluoride and phenol compounds. Betel leaves contain 4.2% essential oil and most of its components consist of betephenol which acts as an antibacterial agent besides that betel leaves contain antiseptic substances that can kill germs. The purpose of our research is to find out how the piper clean manufacturing process is and to find out the piper clean quality test. From the results of organoleptic tests conducted on 36 respondents, the Piper Clean that is most preferred by respondents is piper clean on the A20B10 variable with betel leaf extract: vinegar ratio of 200 ml: 100 ml. which has the characteristics of brown color, distinctive aroma of betel leaves and is very much liked by respondents. In addition to the organoleptic test, the results of our study were tested at LPPT UGM Yogyakarta with the results that piper clean has a pH of 3.15 with a temperature of 250 C, detergent equivalent of Sodium Dodecyl Sulfate 1492.25. it can be concluded that piper clean is safe to use and effective for floor cleaners